Evaluation of the temperature influence and active acidity of the solution on the recovery of dry powder from fruit bodies Pleurotus ostreatus (Jacq) P. Kumm - Vakasova, K. A. (ТДАТУ, 2020)
The improvement of growing technology of Pleurotus ostreatus in Ukraine by improving the quality of plant substrates and the introduction of highly effective strains in industrial crops allows obtaining high yields throughout the year. The increase in the amount of mushroom raw material determines the development of new directions of fruit bodies processing, in particular the production of mushroom powder which is successfully used to enrich everyday products: bread, pasta, soups, etc. But the use of powders for some foods: sauces, the pate filling for pies needs to be restored. Unfortunately, there is no scientific data on the optimal modes of this process.
Keywords: improvement of growing technology of; introduction of highly effective strains; improving the quality of plant substrates